Fundamental understanding of high-capacity lithium-excess cathodes with disordered rock salt structure. (30th May 2021) - Lin, Hao; Moreno, Beatriz; Kucuk, Kamil; Zhang, Sensen; Aryal, Shankar; Li, Zheng; Segre, Carlo U.; Rodriguez, Jassiel; Puthusseri, Dhanya; Cai, Lirong; Jiao, Xuechen; Pol, Vilas G.
Abstract: As a new class of lithium rich cathodes, disordered rock-salt cathodes have been of primary interest, because of their ability to deliver a promisingly high capacity up to 300 mA h/g. Nevertheless, some fundamental issues are yet to be fully understood and a comprehensive mastering of their solid-state chemistry, kinetics and thermal stability is required. Here, we select a high capacity cation-disordered positive electrode- Li1.2 Ni0.4 Nb0.4 O2 as a model compound to study intrinsic reaction mechanism, including charge compensation mechanism, kinetics, thermal stability, and structural evolution. By combining soft and hard X-ray absorption spectroscopy (XAS), X-ray photoelectron spectroscopy (XPS) with operando and ex-situ differential scanning calorimetry (DSC), galvanostatic intermittent titration technique (GITT), cyclic voltammetry (CV), and X-ray diffraction (XRD), we present holistic information on disordered rock-salt cathode. This work provides beneficial insights into designing and tailoring new positive electrodes with disordered rock-salt structure.